1998
DOI: 10.1002/abio.370180309
|View full text |Cite
|
Sign up to set email alerts
|

Production of extracellular enzymes by two Pleurotus species using banana pseudostem biomass

Abstract: INDIA SummaryThe degradation of lignocellulosic biomass of banana pseudostem was investigated during solid state fermentation (SSF) by P. ostreutus and P.sujor-cuju. Both organisms proved to be efficient degraders of banana pseudostem biomass. P.ostreutus degraded hemicellulose (40% of dry weight., d.w.) better than cellulose (17.5% of d.w.) and lignin (10% 0f.d.w.). P. sujor-cuju also degraded hemicellulose (31% of d.w.) better than cellulose (12.4% of d.w.) and lignin (6% of d.w.). In both cases, a preferent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 32 publications
2
12
0
Order By: Relevance
“…These values are in accordance with the literature (STURION, 1994;GHOSH et al, 1998). It can be seen that the substrate presents a low level of digestibility (15.40%).…”
Section: Resultssupporting
confidence: 80%
“…These values are in accordance with the literature (STURION, 1994;GHOSH et al, 1998). It can be seen that the substrate presents a low level of digestibility (15.40%).…”
Section: Resultssupporting
confidence: 80%
“…This indicates that both species of mushroom were more effective in degrading cellulosic content of paddy straw and sorghum stalk rather than banana pseudostem. The degradation of lignocellulosic biomass of banana pseudostem by P.ostrreatus and P. sajor-caju [30] indicated that both organisms degraded hemicellulose better than cellulose.…”
Section: Discussionmentioning
confidence: 98%
“…Makkar et al [33] reported that the β-glucosidase enzyme is part of an enzymatic complex in Lentinus edodes, which also comprises MnP and laccase, where the hydrolase actively participates in the carbohydrates mobilization. Lower activities of this enzyme were produced by P. ostreatus and P. sajor-caju cultivated in banana waste: 0.090 U/mL and 0.087 U/mL, respectively [34].…”
Section: Discussionmentioning
confidence: 99%